fq-Derivation of BP-Algebras - Sri Gemawati; Mashadi Mashadi; Musraini M; Elsi Fitria (Journal of the Indonesian Mathematical Society, 2023)
First, this article presents the definition of left-right derivation and right-left derivation in BP-algebra, and their characteristic are explored. Then, we define the concept of inside and outside fq-derivation of BP-algebras. Finally, their properties are explored. Furthermore, the notion of fq-derivation within BP-algebra is synonymous with B-algebra; however, they do exhibit variations in their respective characteristics.